Hypoxic Tolerance of the Young ones of Sea Bass, Lates calcarifer (Bloch) - S.L., Sreelatha (Fishery Technology, 2025)
Maximum tolerance to hypoxia until asphyxiation (loss of equilibrium) in the case of young ones of sea bassÂ LatesÂ calcarifer was found in sea water, brackish water and freshwater at 30oC and 350C. The hypoxic tolerance observed was comparatively high in sea water, followed by brackish water and freshwater at both 30oC and 350C. The tolerance limit observed was more in sea water, possibly due to less osmoregulation in the natural habitat or due to the metabolic homeostasis.